Regulation of Exogenous Strigolactone on Storage Substance Metabolism and Endogenous Hormone Levels in the Early Germination Stage of Rice Seeds Under Salt Stress - Jianqin Zhang; Dianfeng Zheng; Naijie Feng; Aaqil Khan; Rui Deng; Jian Xiong; Linchong Ding; Zhiyuan Sun; Jiahuan Li; Xiaohui Yang; Chen Wu (Antioxidants)
Salt stress inhibits rice seed germination. Strigolactone (GR24) plays a vital role in enhancing plant tolerance against salt stress. However, GR24’s impact on the metabolism of stored substances and endogenous hormones remains unclear. This study investigated the impact of exogenous GR24 on the metabolism of stored substances and endogenous hormones during the early stages of rice seed germination under salt stress. The results showed that salt stress significantly reduced the germination rate, germination potential, germination index, radicle length, germ length, and fresh and dry weights of the radicle and germ under salt stress. Pre-treatment (1.2 μmol L−1 GR24) significantly reduced the inhibition of salt stress on rice seed germination and seedling growth. GR24 promoted the decomposition of starch by enhancing the activities of α-amylase, β-amylase, and total amylase and improved the levels of soluble sugars and proteins and the conversion rate of substances under salt stress. GR24 effectively enhanced the activities of superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX); increased ascorbic acid (ASA) and glutathione (GSH) levels; and reduced malondialdehyde (MDA) content. This reduced the oxidative damage of salt stress. Furthermore, GR24 significantly increased the contents of strigolactones (SLs), auxin (IAA), gibberellin (GA3), cytokinin (CTK) as well as IAA/ABA, CTK/ABA, GA/ABA, and SL/ABA ratios and reduced abscisic acid (ABA) levels. The current findings indicate that GR24 effectively mitigates the adverse impact salt stress by regulating antioxidant enzyme activity and endogenous hormone balance.